Contact and complexity in English varieties: The influence of speaker numbers on syntheticity and grammaticity - Katharina Ehret (PLoS ONE, 2026)
Empirical research on language complexity has shown that languages and varieties can and do differ in their complexity. One of the key triggers responsible for this observed variation is language contact as non-native acquisition. The influence of language contact on complexity is, however, not uncontroversial: While a number of large-scale typological studies have reported that language contact decreases complexity, others find no such effect in their data. This paper offers a corpus-based perspective on the influence of language contact on morphosyntactic complexity in an English-varieties context. Precisely, I model the effect of the number of native speakers, the proportion of non-native speakers and language type–a theoretical construct based on the sociolinguistic contact history of the varieties–in a corpus database of 25 spoken English varieties. Morphosyntactic complexity is here operationalised as the number of bound grammatical markers (syntheticity) and the total number of explicit grammatical markers (grammaticity). The models show that the number of native speakers negatively correlates with syntheticity. However, contrary to theoretical expectations, the proportion of non-native speakers shows a weak positive effect on syntheticity. None of the speaker-related triggers influences grammaticity. Only language type shows a consistent negative effect on both syntheticity and grammaticity indicating that historic language contact scenarios do impact complexity. The crucial question, then, is what (non-)native speaker numbers really represent and if they are a (good) proxy for language contact. Overall, the results corroborate the controversial findings in the typological literature highlighting the importance of how complexity is operationalised.